2022
DOI: 10.3390/ijerph19063275
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Effect of County Carbon Emissions and Economic Growth in China: Empirical Evidence from Jiangsu Province

Abstract: Under the pressure of low-carbon development at county level in China, this paper takes Jiangsu province as an example to analyze the relationship between economic growth and carbon emissions, aiming to provide a reference for the low-carbon development in Jiangsu and other regions in China. Based on the county-level panel data from 2000 to 2017, this paper uses the Tapio elasticity model and environmental Kuznets curve model, and focuses on the differences in regional economic development and the impacts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Second, existing studies on carbon emissions and land use are mostly limited to the national, provincial, or the municipal scale, and little attention is paid to the county-level emissions, which makes it difficult to accurately formulate carbon reduction measures. Third, among the studies on decoupling, the existing studies mostly analyzed the relationships between carbon emissions and economic growth [ 56 , 57 , 58 , 59 ], the decoupling relationship between China’s net carbon emissions and construction land remains unclear. Little is known about the impact of the expansion or reduction of construction land on carbon emissions and the driving factors of the decoupling between the two factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, existing studies on carbon emissions and land use are mostly limited to the national, provincial, or the municipal scale, and little attention is paid to the county-level emissions, which makes it difficult to accurately formulate carbon reduction measures. Third, among the studies on decoupling, the existing studies mostly analyzed the relationships between carbon emissions and economic growth [ 56 , 57 , 58 , 59 ], the decoupling relationship between China’s net carbon emissions and construction land remains unclear. Little is known about the impact of the expansion or reduction of construction land on carbon emissions and the driving factors of the decoupling between the two factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of counties, Ji and Xue., 2022 investigated the decoupling of carbon emissions in Jiangsu Province, China, and concluded that economic growth and carbon emission reduction did not always happen at the same time. However, the decoupling effect of carbon emissions in counties gradually increased over time Ji andXue., 2022. Liu et al (2021), enriched Energy-Economy-Environment (3E) system theory.…”
Section: The Relationship Between Carbon Emissions and Economic Growthmentioning
confidence: 99%
“…To address the growing environmental problems, the central and provincial governments have developed several action plans and targets in recent years to control the urgency of environmental issues, namely air, water, and soil pollution, as well as carbon emissions. For example, the state has mandated that 93% of urban water supplies must meet “drinking water” standards by 2020 [ 12 ], strict air quality targets have been set in regions such as the Yangtze River Delta and the Pearl River Delta [ 12 ], there has been an implementation of documents on environmental taxes and cap-and-trade policies based on market policies [ 13 , 14 , 15 , 16 ], China has committed to carbon neutrality and carbon peaking targets [ 17 , 18 , 19 ], etc. The implementation of the above plans and actions will help us to comprehensively address the serious environmental problems that China faces with respect to its economic growth.…”
Section: Introductionmentioning
confidence: 99%